Analysis of energy and emission metrics for an experimental turbojet engine by regression approach - Ezgin, Hamza; Kirmizi, Mehmet; Celik, Umit; Aygun, Hakan (Taylor & Francis Inc, 2025)
The common usage of micro turbojet engines has sparked attention on these systems due to their unique advantages, which enable insight into the characteristics of different scaled turbojet engines. In this study, 930 data points regarding an experimental turbojet engine are obtained by operating the JetCAT P80 micro turbojet engine at minimum and maximum power settings under stationary conditions. These data are employed to model engine performance parameters including air mass flow, fuel flow, thrust, specific fuel consumption, exhaust gas temperature and CO2 emissions depending on turbine RPM. By increasing shaft speed from 35 krpm to 125 krpm, air mass flow is computed to be between 0.054 kg/s and 0.239 kg/s while CO2 emissions range between 3.22 g/s and 14.87 g/s. On the other hand, the net thrust of micro turbojet engine ranges from 4 N to 78 N whereas specific fuel consumption of the engine varies from 0.2095 kg/(N.h). to 0.9537 kg/(N.h). Furthermore, exhaust gas temperature changes from 562 degrees C to 725 degrees C. The obtained data are modeled using a regression method based on the turbine RPM by using the curve fitting tool in the MATLAB environment. The results of the quadratic modeling show that the R2 of exhaust gas temperature is calculated as the lowest with 0.812, while R2 of air mass flow and CO2 emissions are measured more than 0.995 respectively thanks to quadratic modeling. It is thought that the obtained database can be used to map the engine's performance. Thus, by determining the operating points that provide less fuel consumption, it can contribute to the reduction of greenhouse gas emissions.
Keywords: Engine performance; micro turbojet; regression modeling; specific fuel consumption; thrust